The Internet [technology 1999 analysis and forecast]. - Lange, L. (IEEE spectrum)
Despite 1998's early doom'n'gloom projections of a gigantic logjam-or even a complete Net shutdown-the giant network of networks survived remarkably well. In fact, the Net has grown more robust despite its marked growth. Ambition keeps paying off. The bandwidth and experimental multimedia plans ushered in last year by several bandwidth firms are moving full speed ahead. Additionally with infrastructure technologies in place, and Java on track as a de facto Internet language standard, several Net engineers are again using the Internet as their own techno-playground